Automated part inspection by image processing system in vehicle part manufacturing - Akekachai Pannawan; Supattarachai Sudsawat (My University, 2017)
บทคั ดย อในการผลิ ตชิ ้ นส วนยานยนต คุ ณภาพถื อเป นสิ ่ งสํ าคั ญที ่ ผู  ผลิ ตต องคํ านึ งถึ ง งานวิ จั ยนี ้ จึ งมี วั ตถุ ประสงค ใน การพั ฒนาระบบตรวจสอบคุ ณภาพแบบอั ตโนมั ติ โดยการประยุ
Keywords: Automated X-ray inspection; Industrial Vision Systems and Defect Detection